2010
DOI: 10.1586/eci.10.22
|View full text |Cite
|
Sign up to set email alerts
|

Once-daily mesalamine granules for ulcerative colitis

Abstract: Mesalamine extended-release capsules (Apriso [Salix Pharmaceuticals, Raleigh, NC, USA]) are the first once-daily mesalamine preparation approved by the US FDA for the maintenance of remission of ulcerative colitis (UC). Each mesalamine extended-release capsule contains granules of a mesalamine-polymer matrix that are coated with a pH-sensitive resin. This design begins releasing mesalamine (0.375 g) once the pH is more than 6 in the ileum and colon. Two clinical trials have reported that mesalamine extended-re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 34 publications
0
7
0
Order By: Relevance
“…The first OD mesalamine preparation (Apriso; Salix Pharmaceuticals, NC, USA) was approved by the U.S. Food and Drug Administration (FDA) for the maintenance of UC remission 18 . To date, the OD administration of various proprietary forms of 5‐ASA has been proven safe and effective in contemporary clinical trials, 19 and many clinicians have applied this more practical dosing scheme to delayed and sustained release formulations of oral mesalamine.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The first OD mesalamine preparation (Apriso; Salix Pharmaceuticals, NC, USA) was approved by the U.S. Food and Drug Administration (FDA) for the maintenance of UC remission 18 . To date, the OD administration of various proprietary forms of 5‐ASA has been proven safe and effective in contemporary clinical trials, 19 and many clinicians have applied this more practical dosing scheme to delayed and sustained release formulations of oral mesalamine.…”
Section: Discussionmentioning
confidence: 99%
“…The first OD mesalamine preparation (Apriso; Salix Pharmaceuticals, NC, USA) was approved by the U.S. Food and Drug Administration (FDA) for the mainte-nance of UC remission. 18 To date, the OD administration of various proprietary forms of 5-ASA has been proven safe and effective in contemporary clinical trials, 19 and many clinicians have applied this more practical dosing scheme to delayed and sustained release formulations of oral mesalamine. A pharmacokinetic data analysis by Gandia et al 20 also showed that concentrations of 5-ASA and acetylated 5-ASA (Ac-5-ASA) in urinary and fecal excretion and rectal tissue were similar following single or divided daily dosing in 30 healthy volunteers.…”
Section: Discussionmentioning
confidence: 99%
“…Lialda/Mezavant capsules contain additional lipophilic and hydrophilic matrices Multi Matrix System (MMX) within the Eudragit S capsule, with the goal of allowing slower diffusion of the drug through the colon [25]. Apriso also contains a polymer matrix coated with Eudragit L, designed to gradually distribute mesalamine throughout the colon [26]. …”
Section: Pharmacologymentioning
confidence: 99%
“…At 1-year follow-up, 54% of patients on Pentasa were in continued remission as opposed to 46% of patients on sulfa-salazine [45]. Maintenance studies of Apriso reported that 78.9% of patients on Apriso maintained remission compared with 58.3% of the placebo group [26]. The US FDA-approved doses for maintaining remission are as follows: Asacol 1.6 g daily; Lialda 2.4 g daily; and Apriso 1.5 g daily.…”
Section: Clinical Efficacymentioning
confidence: 99%
“…There is also a disconnect between the “FDA‐approved” indications and dosing of these drugs and their use in clinical practice. Only Asacol (Warner‐Chilcott) and Apriso (Salix) have been approved for maintenance of remission in UC, whereas Asacol HD (Warner‐Chilcott) is only approved for 6 weeks use for induction of remission; despite this, all these agents are used long‐term for maintenance of remission in practice 33, 34…”
Section: Current Fda‐approved Therapies For Ibdmentioning
confidence: 99%